Linkage Disequilibrium Between TNF-α-308 G/A Promoter and Histocompatibility Leukocyte Antigen Alleles in Han-Nationality Lung Transplant Recipients From Eastern China - Huijun, Mu; Ji, Zhang; Ping, Xie; Jingyu, Chen; Bin, Zhang (Experimental and clinical transplantation, 2013)
Genes encoding histocompatibility leukocyte antigen (HLA) and proinflammatory cytokines are involved in rejection after organ transplant. The authors explored the association between HLA alleles and the tumor necrosis factor (TNF)- α-308 G/A promoter region in lung transplant recipients of Han nationality from East China. They also evaluated the correlation between TNF-α-308 G/A and the onset of acute rejection after lung transplant. All lung transplant recipients of Han nationality who were admitted into our hospital between August 2004 and July 2011 were included. Patients were divided into 2 groups according to the presence or absence of acute rejection episodes. Genotypes of HLA and single nucleotide polymorphisms of TNF-α-308 G/A were determined using polymerase chain reaction-single specific primer kits. A total of 106 lung transplant recipients were investigated. HLA-A*2 allele was in linkage disequilibrium with TNF-α-308 G allele. HLA-A*33, -B*58 and -DRB1*03 alleles were in linkage disequilibrium with TNF-α-308 A allele. Notably, TNF-α-308 A allele was in complete linkage disequilibrium with HLA-B*58 allele. Furthermore, TNF-α-308 A allele was in linkage disequilibrium with the HLA-A*33-DRB1*03 and HLA-B*58-DRB1*03 haplotypes. Clinical analysis indicated that TNF-α-308 G/A was not associated with onset of acute rejection after lung transplant. TNF-α-308 G/A polymorphism was strongly associated with HLA-A*2, -A*33, -B*58, and -DRB1*03 alleles in our population. HLA genotyping can identify lung transplant recipients carrying the highly productive phenotype of TNF-α-308 A allele, which may provide information on rejection after transplant. However, the authors found that TNF-α-308 A subtype has no correlation with acute rejection after lung transplant.